Neuropsychological Impairment in Acute HIV and the Effect of Immediate Antiretroviral Therapy. (1st December 2015) - Kore, Idil; Ananworanich, Jintanat; Valcour, Victor; Fletcher, James L. K.; Chalermchai, Thep; Paul, Robert; Reynolds, Jesse; Tipsuk, Somporn; Ubolyam, Sasiwimol; Rattanamanee, Somprartthana; Jagodzinski, Linda; Kim, Jerome; et al.
Abstract : Objective: To investigate neuropsychological performance (NP) during acute HIV infection (AHI) before and after combination antiretroviral therapy (cART). Design: Prospective study of Thai AHI participants examined at 3 and 6 months after initiation of cART. Methods: Thirty-six AHI participants were evaluated pre-cART at median 19 days since HIV exposure and 3 and 6 months after cART with the Grooved Pegboard test, Color Trails 1 & 2 (CT1, CT2), and Trail Making Test A. Raw scores were standardized to 251 age- and education-matched HIV-uninfected Thais. To account for learning effects, change in NP performance was compared with that of controls at 6 months. Analyses included multivariable regression, nonparametric repeated measures analysis of variance, and Mann–Whitney U test. Results: Baseline NP scores for the AHI group were within normal range (z-scores range: −0.26 to −0.13). NP performance improved on CT1, CT2, and Trail Making Test A in the initial 3 months ( P < 0.01) with no significant change during the last 3 months. Only improvement in CT1 was greater than that seen in controls at 6 months ( P = 0.018). Participants who performed >1 SD below normative means on ≥2 tests (n = 8) exhibited higher baseline cerebrospinal fluid HIV RNA ( P = 0.047) and had no improvement after cART. Conclusions: Most AHI individuals had normal NP performance, and early cART slightly improved their psychomotor function. However, approximately 25% had impaired NP performance, which correlated with higher cerebrospinal fluid HIV RNA, and these abnormalities were not reversed by early cART possibly indicating limited reversibility of cognitive impairment in a subset of AHI individuals.